AN IDENTIFYING OF CODE MIXING USED BY THE STUDENTS’ OF ENGLISH STUDY PROGRAM IN THEIR TEACHING PRACTICE VIDEO - Ninit Massagala Saman; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Language holds an important role in human life because it is an effective way for contacting purposes in their lives. It is a tool of communication which means that the language itself beings to understand and cannot be separated with human because language is one of the ways for human to communicate to each other. Language is also used to show ideas, feelings, and thoughts to others. This research aims to analyze code collected using an observation sheet regarding to the types of code mixing and video to gather the data in use of code mixing used by the students’ of English study program in their teaching practice video. This research used qualitative research method with descriptive qualitative. The data for this research were the code mixing in the classroom. The subject of the study is the students’ of English study program. After collecting the data, the data were analyzed through some steps namely data reduction, data display based on code mixing categories and conclusion drawing. The result of this research showed that there are two types of code mixing used by the students’ of English study program. The types which occurred in the students’ utterance is intra sentential code mixing (92,7%)and intra lexical code mixing (7,3%). In conclusion, bilingual and multilingual speakers allowed using two languages at a particular time for supporting ideas. For example, an idea cannot be explained in one language, then another language will be need to clarify it.Key Words: Code Mixing, Descriptive Qualitative Method, Teaching Practice Video.